In silico approach to study and functionally analyze interferon regulated genes - Tokovenko, B.T.; El'skaya, A.V.; Obolenskaya, M.Yu. (Біополімери і клітина, 2007)
Finding genes which have biologically meaningful ISRE (interferon-stimulated response element) is important for better understanding of the Jak-STAT activated cellular IFN response. We used transcription factor binding site (TFBS) search with gene orthology filtering to find putative ISREs in the promoters of protein-coding genes of Rattus norvegicus, and used Gene Ontology (GO) analysis to check the validity of ISRE search results in terms of biological meaning. A total of 23286 promoters of rat genes were analyzed. ISRE search with 80 % threshold produced 5214 sites in 4571 promoters. 850 ISREs in 768 promoters passed orthology filtering. Distribution of ISREs along the promoter in 768-gene set reveals 3 regions of ISRE localization: 0 to –250, –250 to –550, and above –550 relative to TSS (transcription start site). It is not yet known whether ISRE localization has any functional implications. Using BayGO, a total of 84 GO terms were found to be enriched at P < 0.05 in the 768-gene set. Among these categories some are directly related to known IFN actions (positive regulation of B cell differentiation, humoral immune response, response to virus, cell differentiation etc.). 768 gene set was compared to the 4571 gene set using GO Tree Machine. Such categories as cell differentiation, cell cycle, regulation of cell cycle, viral life cycle and some others were found to be enriched, and belong to the well-known domains of interferon actions. Their relative enrichment is an indirect indication that the applied orthology filtering does increase the quality of results. Gene orthology-based filtering of the initial TFBS search results was shown to produce viable and expected results. Genes identified in this research as containing ISRE in promoters will be used to seed the construction of the IFN-a-induced gene regulatory network.